“One Team One Family”; Interprofessional Collaboration in Supporting Pregnant Women to Reduce Anxiety - Sumarni, Sri; Ulfiana, Elisa; Octaviani, Dhita Aulia; Kumorowulan, Suryati (Media Karya Kesehatan, 2024)
The Maternal Mortality Rate in Central Java is still relatively high. The main causes of maternal death in Central Java are hypertension in pregnancy, bleeding, heart problems, infections, and metabolic disorders. Pregnancy is a vulnerable period and there are many physiological and psychological problems. The anxiety of pregnant women needs to be prevented to prepare for the delivery and parenting process. There are many impacts that occur if the anxiety of pregnant women is not addressed to the delivery and childcare process during the postpartum period. There needs to be cooperation that involves many professions in assisting pregnant women. The purpose of this activity is to implement maternal assistance during pregnancy, childbirth, postpartum, and parenting to reduce anxiety with interprofessional collaboration methods. The implementation of the activity is through direct mentoring. Observation was carried out for 3 months from July to September 2021. The collection of pretest and posttest data was carried out using a questionnaire given to 19 pregnant women in Banyumanik Semarang Central Java. The observation method was carried out during the assistance of pregnant women once during pregnancy, once during childbirth, once during the postpartum period, and once parenting. The one-team-one-family service team consists of lecturers and students of the midwifery, nursing, dental and oral health study programs. The activity involved village officials at the sub-district, sub-district, and health center levels. The participating professions are midwives, nurses, general practitioners, health survey officers, and health cadres. The results of community service show that the level of anxiety of pregnant women has decreased.  The majority of pregnant women experienced complaints such as fear of their own thoughts 12 (62.2%), cramps 9 (47.4%), difficulty sleeping and resting 7 (36.8%). Pregnant women were satisfied with the explanation, communication, appearance, attitude, and companion skills during the activity.   Interprofessional collaboration is effective to prepare pregnant women to go through childbirth, breastfeeding and childcare.Kata kunci: interprofessional collabroration; one team one family; Assistance